Game vs. practice differences in external load in U16 and U18 women`s basketball players - Cabarkapa, D. V.; Cabarkapa, D.; Nagy, D.; Balogh, L.; Laczko, T.; Ratgeber, L. (Sports, 2025)
The purpose of the present study was twofold: (i) to examine within-group differences in external load metrics during practice and official competition, and (ii) to examine between-group differences in external load metrics across the U16 and U18 levels of play. A total of thirty-six female athletes participated in the present study, of which nineteen were U16 and seventeen were U18 basketball players. The athletes wore an inertial measurement unit system (Kinexon) sampling at 20 Hz during practice and official games. The average values for each external load metric across ten practices and five games were used for performance analysis. Dependent and independent t-tests were used to examine within- and between-group statistically significant differences, respectively (p < 0.05). The findings reveal that the external load placed on the athletes during the game (e.g., distance covered, average speed, total number of accelerations and decelerations) was considerably greater than the external load during practice sessions, both on the U16 and U18 levels of play. Conversely, while the game-induced external load remained consistent across the two competitive levels, U18 players tended to spend more time and cover more distance in low-speed zones than in high-speed zones during practice, compared to their U16 counterparts, suggesting their superior movement efficiency.